Protection against Crimes in Islamic Jurisprudence : Investigation and Analysis (Islamic Sciences Journal, 2023)
ABSTRACTThe study examines one of the significant societal issues for which Allah Almighty has imposed severe penalties in order to deter others and attain divine justice among humans who should live tranquil and secure lives. The purpose of the study is to solve societal challenges, such as how to prevent slipping into sins, transgressions, and criminality via individual self-control. The significance of the study seems to be pertinent, as it pertains to elucidating an important jurisprudential problem in the lives of persons, namely the need of avoiding criminal behavior. The researcher attempts to enlighten individuals that they are prone to committing crimes and to warn them in this life and hereafter.  The research falls into an introduction, three sections, and a conclusion. Although the introduction situates the study in its background, the other three sections focus on the essence of the subject, namely crime, its prevention, and its treatment. The conclusion summarizes the study's most significant results.
Keywords: Protection, crimes, methods of restriction, methods of prevention, repressive methods